Hookworm - Related cutaneous larva migrans: Case report - Siham Boularbah; Zakia Douhi; Sabrina Oujidi; Mariam Soughi; Sara Elloudi; Hanane Baybay; Fatima Zahra Mernissi (Our Dermatology Online, 2023)
Hookworm-related cutaneous larva migrans is caused by the intradermal migration of soil-dwelling filariform larvae of dog and cat hookworms, most commonly Ancylostoma, usually develop itchy skin lesions, usually consisting of migrating superficial serpiginous traces, or sometimes stationary follicular eruptions. The plantar topography or on the regions of the body in contact with the sand of the beaches of the Antilles, West Africa and East Asia, the presence of fine and not very mobile serpiginous furrows and eczematization with vesiculobullous eruption, are characteristic. There are misleading profuse forms such as pseudo-folliculitis. We present a Moroccan patient who developed the disease after their return from and who responded well to treatment with albendazole.